Evaluation of motor performance in school ages through Lincoln-Oseretsky motor tests - J. Rosa; L. P. Rodríguez; S. Márquez (Asociación Española de Ciencias del Deporte, 2010)
Motor performance was evaluated on the Lincoln-Oseretsky Motor Development Scale in a group of 1083 elementary school children (588 boys and 485 girls), aged 6 to 12 years. Motor development of the studied population was within normal range, with no difference between chronological age and motor age at any age. Overall, a fairly linear change with age was found in most of the motor tasks. Although significant age and sex differences were found on most of the motor tests, it appears that age generally was related more to performance than was gender. Sex-differences in the scores for the different tests were scarce, reduced to specific ages and indistinctly favouring boys or girls. All children were enrolled in coeducational classes. This would reduce the importance of sociocultural background as a limiting factor for girls performance. KEY WORDS: Motor development, motor performance, motor tests, Lincoln-Oseretsky tests